Draft Eighth Five Year Plan (1990-95) Andhra Pradesh Volume-III (Tables) - Planning Commission (Planning Commission, 1990)
Outlay and expenditure during Seventh Five Year Plan Physical Targets and achievements during Seventh Five Year Plan Draft Eighth Plan (1990-95) Proposals for Programmes/Projects - Maximising benefits from the existing capacity (As on 31.3.1990) Draft Eighth Year Plan (1990-95) and Annual Plan 1990-91 and 1991-92 - Outlays by Heads of Development Statement Regarding Externally Aided Projects-Draft Eighth Plan Draft Eighth Five Year Plan - Tribal Sub-Plan (TSP)Financial Outlays/Physical Targets: Proposals for TSP 1990-91 and 1991-92 Statement showing Employment (Scheme-wise) in the Seventh/Eighth Plan with corresponding figures of Expenditure/Outlay Rural Component of Draft Eighth Plan and Annual Plans 1990-91 and 1991-92-Outlays.
Finance and Planning (PLG. Wing) Department, Government of Andhra Pradesh